2019
DOI: 10.1080/15140326.2019.1692581
|View full text |Cite
|
Sign up to set email alerts
|

Foreign currency invoicing of domestic transactions as a hedging strategy: evidence for Uruguay

Abstract: This study is an empirical analysis of the factors associated with the use of the US dollar for the invoicing of domestic transactions, which is a common practice of Uruguayan firms. Using a novel dataset we find that both the input and debt structure of firms are relevant for determining their currency of invoicing. Intuitively, firms will generate cash flows in US dollar if they have to make expenditures in foreign currency, either because they use imported inputs or if they cover debt services with currency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 15 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…However, Bartram and Bodnar (2012) investigated non-financial firms and suggested that stock returns relation with the exchange rate exposure was conditional; however, the return impact was significantly linked with the sign and size of change in exchange rates, the source of time variation in currency return due to fluctuations. Licandro and Mello (2019) further endorsed that the association between stock returns and exchange rate exposure was although validated by the cash flow effect. In these cases, exchange rate fluctuation affected cash flows of the companies in international business and the stock returns of the U.S., Japan and Germany varied by fluctuations in exchange rates due to macroeconomic factors and fluctuations in real terms of trade.…”
Section: Review Of Studies Relating Foreign Exchange Exposure and Firm Related Foreign Exchange Exposuresmentioning
confidence: 95%
“…However, Bartram and Bodnar (2012) investigated non-financial firms and suggested that stock returns relation with the exchange rate exposure was conditional; however, the return impact was significantly linked with the sign and size of change in exchange rates, the source of time variation in currency return due to fluctuations. Licandro and Mello (2019) further endorsed that the association between stock returns and exchange rate exposure was although validated by the cash flow effect. In these cases, exchange rate fluctuation affected cash flows of the companies in international business and the stock returns of the U.S., Japan and Germany varied by fluctuations in exchange rates due to macroeconomic factors and fluctuations in real terms of trade.…”
Section: Review Of Studies Relating Foreign Exchange Exposure and Firm Related Foreign Exchange Exposuresmentioning
confidence: 95%
“…However, prior research has found a strong empirical relationship between the size of the firm and the share of debt denominated in foreign currency (see, for 16 Although real estate are non-tradable, their demand can have an international component as various foreign investors buy properties in many of the countries, in particular in touristic destinations. example, Kamil, 2012;Licandro and Mello, 2019;Richers, 2019;Salomao and Varela, 2019).…”
Section: Price Dollarization At the Micro Levelmentioning
confidence: 99%